Mathimagicians Quest: Applying game design concepts to education to increase school engagement for students with emotional and behavioral disabilities - Bond, Lauren (My University, 2015)
There are concerns among researchers and education professionals that students in our classrooms are bored, unmotivated and disengaged from school. There is substantial research showing low school engagement is linked to poorer school outcomes including: increased risk for drop-out, reduced academic performances and poorer well-being. Conversely, research indicates students with higher engagement have increased academic success, better well-being and higher rates of school completion. This link between school engagement and school outcomes is particularly concerning for students with disabilities who are at higher risks for low engagement, as compared with their general education peers. Though similarly cognitively challenging to school, games are typically highly engaging and students are willing to spend many hours engaged in playing games. Gamification has been proposed a means of applying game concepts to education in order to make school activities more engaging. This study explores the application of gamification to education, and the impact on student engagement. This study implements a gamification structure that can be applied across curriculum areas, which modifies student assessment and feedback using mechanics from role-play games. The gamified system was utilized in a middle school classroom with students with Emotional/Behavior Disabilities in order to gamify math instruction over a two week unit. The study found no statistically significant results, but qualitative findings suggested that future research, with a larger sample and longer unit, into the impact of gamification on student engagement is warranted. Additionally, this study provides a template and direction for practitioners to consider if applying gamification in their classroom.
Thesis (Master's)--University of Washington, 2015
Keywords: engagement; gamification; Education; education - seattle